2015
DOI: 10.1177/1534735415580676
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Asian Ginseng (Panax Ginseng) for Cancer-Related Fatigue

Abstract: Introduction and Objective. Cancer-related fatigue (CRF) is the most common and severe symptom in patients with cancer. The number and efficacy of available treatments for CRF are limited. The objective of this preliminary study was to assess the safety of high-dose Panax ginseng (PG) for CRF. Methods. In this prospective, open-label study, 30 patients with CRF (≥4/10) received high-dose PG at 800 mg orally daily for 29 days. Frequency and type of side effects were determined by the National Cancer Institute’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Specifically, red ginseng was associated with improved emotional functioning and decreased symptoms such as fatigue, nausea and vomiting, and dyspnea in the EORTC QLQ-C30, reduced severity of worst fatigue and interference in the BFI, decreased interference affecting enjoyment of life in the BPI, reduced anxiety in the HADS and improved daytime somnolence in the MOS-SS. These results suggest that red ginseng may improve quality of life after chemotherapy in patients with EOC, which can be supported by previous studies [ 41 , 42 , 43 ]. Although there is a lack of evidence about underlying mechanisms which link genotoxicity and HRQL in EOC patients, oxidative stress and chronic inflammation is known to be related with public health [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, red ginseng was associated with improved emotional functioning and decreased symptoms such as fatigue, nausea and vomiting, and dyspnea in the EORTC QLQ-C30, reduced severity of worst fatigue and interference in the BFI, decreased interference affecting enjoyment of life in the BPI, reduced anxiety in the HADS and improved daytime somnolence in the MOS-SS. These results suggest that red ginseng may improve quality of life after chemotherapy in patients with EOC, which can be supported by previous studies [ 41 , 42 , 43 ]. Although there is a lack of evidence about underlying mechanisms which link genotoxicity and HRQL in EOC patients, oxidative stress and chronic inflammation is known to be related with public health [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…There are currently few studies about GOP in human. A preliminary report declared that the regular dosage of ginseng was under 1 g/day [40]. However, a randomized, double-blinded, placebo-controlled trial showed that administering 2 g/day of ginseng extract was beneficial to patients with idiopathic chronic fatigue [14].…”
Section: Discussionmentioning
confidence: 99%
“…The present research focus on ginseng ( Panax ginseng C. A. Mey), which is a perennial herb, with a root height of 30–60 cm, hypertrophic, fleshy, yellow-white, cylindrical or spindle-shaped, with a slightly-branched, short, upright rhizome (reed) (Figure 1 ). Currently, dry ginseng root is used worldwide to treat diabetes (Gui et al, 2016 ), cancer-related fatigue (Yennurajalingam et al, 2015 ), cardiovascular disease (Kim, 2012 ), stroke (Rastogi et al, 2014 ), and other diseases.…”
Section: Introductionmentioning
confidence: 99%